2020
DOI: 10.17221/1/2020-rae
|View full text |Cite
|
Sign up to set email alerts
|

Influence of magnetised irrigation water on the fertigation process and potato productivity

Abstract: An experiment was conducted for two seasons on a farm in the Mit Kenana village, Qalyobia, Egypt. The aim was to study the influence of a magnetised water technology on the fertilisers during irrigation (fertigation) and its impact on the water, soil as well as the yield and yield components for potatoes. The experiment included: Normal water (NM), magnetic water (MW), adding fertiliser before (FMW) and after magnetism (MWF). The results indicated that irrigation with magnetised water and then adding fertilise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 17 publications
5
16
0
Order By: Relevance
“…The results have shown that MTW changes the distribution of salts between soil layers reducing their content in the upper layers which are more important for agriculture. Magnetic water treatment technologies are needed to reduce the rate of salt accumulation and improve the leaching of salts below the root zones of salt-sensitive agricultural crops and in general in salt-affected soils under arid conditions [24] and [35]. An additional interesting finding of this study, was that the total distribution area and volume of water, soil field capacity and consequently the available water in the investigated sandy soil irrigated with magnetized water was higher than soils irrigated with unmagnetized water.…”
Section: Impacts Of Irrigation With Magnetized Water On the Investigamentioning
confidence: 60%
See 3 more Smart Citations
“…The results have shown that MTW changes the distribution of salts between soil layers reducing their content in the upper layers which are more important for agriculture. Magnetic water treatment technologies are needed to reduce the rate of salt accumulation and improve the leaching of salts below the root zones of salt-sensitive agricultural crops and in general in salt-affected soils under arid conditions [24] and [35]. An additional interesting finding of this study, was that the total distribution area and volume of water, soil field capacity and consequently the available water in the investigated sandy soil irrigated with magnetized water was higher than soils irrigated with unmagnetized water.…”
Section: Impacts Of Irrigation With Magnetized Water On the Investigamentioning
confidence: 60%
“…The reason that soil moisture was higher for the magnetized irrigation water might be due to that water molecules are released to make the water more cohesive as influenced by hydrogen bonds and Van der Waals forces. Thus, the water molecules were easily attached to soil particles and did not leach to lower depths and also the water molecules easily penetrated into the micro spaces of soil particles and were thus impeded from moving to the lower depths [24] and [35].…”
Section: Figure (4) Three Dimensional Soil Moisture Distribution Andmentioning
confidence: 99%
See 2 more Smart Citations
“…In modern agriculture, magnetic treatment of water and fertilizer irrigation has been the underlying physical technology to increase crop yields [1]. Some studies have confirmed that irrigation with magnetized water and fertilizer can enhance the ability of some crops to absorb nutrients [1][2][3],and also improve some specific goals [4][5][6][7][8].In fact, the essence of magnetized water and fertilizer is that under the action of a magnetic field, its physical and chemical properties, such as surface tension coefficient, viscosity, conductivity, PH value, will change [9][10][11], this has an impact on the growth of crops. This article hopes that by predicting the physical and chemical properties of magnetized water and fertilizer(PCPMWF ) , it will further help to explore the impact of magnetized water and fertilizer irrigation on crops.…”
Section: Introductionmentioning
confidence: 99%